Self Assessment Exercises in Intensive Care Medicine. Issue 2 (1st June 2009) - Henning, J; Hunt, PAF
Abstract : Intensive Care Medicine (ICM) is no longer the exclusive preserve of anaesthetists as both emergency medicine and general medicine trainees now also train in this increasingly important speciality. This edition of the JRAMC self assessment question series serves to cover some of the current 'hot topics' in ICM and enables readers with experience of ICM to test their knowledge as well as educating junior trainees in relevant subjects that they may be unfamiliar with. Similarly, the Focus On . . . . series of papers elsewhere in this journal demonstrate the increasing importance of ICM in the deployed Field Hospital setting.